The effect of excessive coca-cola consumption on the development of dental erosions - Ignjatović Zorica; Stojšin Ivana; Brkanić Tatjana; Lončar Jovana (Serbian Medical Society - Dental Section, Belgrade, 2012)
The last few years have brought many changes in daily habits and overall lifestyle of human population, which is accompanied by increased exposure to acidic substances and increased consumption of acidic food. Regardless of the numerous warnings given by the World Health Organization about the harmful effects of carbonated beverages on general health, popularity and frequency of Coca-Cola usage have been growing steadily. Numerous epidemiological studies have demonstrated its potential negative effects on tooth structure. Good health education in developed countries has improved the awareness of the importance of oral hygiene; on the other hand, greater consumption of soft drinks has increased the incidence of dental erosions. Effective prevention and monitoring of dental erosions mostly depend on the knowledge about the etiology and early recognition of signs and symptoms of these lesions in clinical practice.